Industrialization and regional income inequality: agriculture transformation. Issue 1 (March 2021) - Rauf, R A; Suparman,; Husnah,; Halwi, M D; Pratama, M F; Mayapada, A G; Arsyad, M
Abstract: Industrialization and income inequality is a crucial issue in developing countries. This paper analyzes the level of income inequality in Morowali and Banggai Regencies, Central Sulawesi, Indonesia. Inequality income is proxied by Gini, Williamson and Theil (GWT) indices. The Gini coefficient was calculated based on data obtained from questionnaires distributed to 150 households. The Williamson index and Theil index were calculated by using the data of gross domestic per capita regional income. The results reveal that the regional income inequality of Morowali and Banggai Regency increased when the economic growth of both regions experienced a significant increase, when the large mining industry began to operate in both areas. The manufacturing and mining industries in have succeeded in shifting the dominance of agriculture sector. The level of income inequality among households and regional has reached a moderate level and tends to fluctuate. Meanwhile, the level of income distribution between regions within regencies is relatively low. The government should consider the impact of industrial presence in areas originally sustained by the agrarian sector in relation to income distribution. Second, the preparation of skilled and educated local workers in facing the industrialization era needs to be conducted